Evaluation of a Combined Neonatal and Obstetric Resuscitation Program in a Resource-Limited Setting. (October 2017) - Edwardson, Jill; Shilkofski, Nicole
Abstract : BACKGROUND: Philippines has some of the highest NMR (14 per 1, 000 live births) and MMR (MMR 220 per 100, 000 live births) in Asia. Prior studies in limited-resource settings have shown efficacy of simulation-based HBB initiatives in improving education and regional stillbirth rates. The HMS program similarly addresses emergency obstetric care. METHODS: Training courses in HBB/HMS were conducted for N=55 midwives in Davao, Philippines, as part of an interventional cohort study. Multiple choice exams and videotaped objective standardized clinical assessments were used to measure knowledge and skills pre- and postintervention. Outcome measures were compared pre- and postintervention using t-test comparison of means. RESULTS: Written knowledge tests revealed a 13% relative improvement in posttest scores ( P <.001). Skill improvement in maternal resuscitation was demonstrated by decrease in average time to administration of uterotonic agent after birth from 95 to 54 seconds ( P <.001) and in neonatal resuscitation by achievement of successful bag mask ventilation by 45% preintervention versus 100% postintervention ( P <.001). DISCUSSION: Combined training in neonatal and obstetric management resulted in increased knowledge and skills for midwives in this resource-limited setting. Next steps include assessment of skill decay curves, rate of uptake of best practices, and longitudinal analysis of regional NMR and MMR.